2023
DOI: 10.5961/higheredusci.1135409
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Preparatory Class EFL Students’ L2 Writing Anxiety

Abstract: The current paper aims to investigate foreign language (L2) writing anxiety levels of Turkish EFL students with regard to their foreign language writing performance, gender, age and language level. The participants were 120 preparatory class students from A1, A2, and B1 levels at a state university in Turkey. The data were collected through an inventory, namely The Second Language Writing Anxiety Inventory by Cheng (2004a), and midterm and final exam scores. According to the results of statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The students might have developed avoidance as an anxietycoping strategy over time as the study results indicated an increasing trend of avoidance behaviour as the year of study advanced. The gender effect has been a controversial issue in writing anxiety research as there are studies asserting no significant effects of gender (Mulyono et al, 2020;Quvanch & Na, 2022;Zerey, 2013), whereas there are also some studies suggesting higher levels of L2 writing anxiety for female learners (Bailey & Almusharraf, 2022;Cheng, 2002;Kırmızı et al, 2015;Keyvanoğlu & Atmaca, 2023). Regarding the year of study, similar results have been yielded in previous research (Cheng, 2002;Quvanch & Na, 2022;Mulyono et al, 2020), while few contradicting findings are also available (Ekmekçi, 2018).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…The students might have developed avoidance as an anxietycoping strategy over time as the study results indicated an increasing trend of avoidance behaviour as the year of study advanced. The gender effect has been a controversial issue in writing anxiety research as there are studies asserting no significant effects of gender (Mulyono et al, 2020;Quvanch & Na, 2022;Zerey, 2013), whereas there are also some studies suggesting higher levels of L2 writing anxiety for female learners (Bailey & Almusharraf, 2022;Cheng, 2002;Kırmızı et al, 2015;Keyvanoğlu & Atmaca, 2023). Regarding the year of study, similar results have been yielded in previous research (Cheng, 2002;Quvanch & Na, 2022;Mulyono et al, 2020), while few contradicting findings are also available (Ekmekçi, 2018).…”
Section: Discussionmentioning
confidence: 62%
“…It is not assessed in any of the national exams (Altınmakas & Bayyurt, 2019), and contemporary and effective approaches to writing have been poorly applied in classroom practices (Graham et al, 2022). In the relevant literature, some studies have found moderate (Kırmızı et al, 2013;Li, 2022;Mulyono et al, 2020;Quvanch & Na, 2022), moderate to high (Genç & Yayli, 2019;Zerey, 2013) and high (Keyvanoğlu & Atmaca, 2023;Rabadi & Rabadi, 2020;Rezaei & Jafari, 2014) levels of writing anxiety, indicating a definite presence of at least moderate levels of learner anxiety in the L2 writing context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations